Selected Topics on Requirements Engineering: Editorial Introduction to the Issue 3 of CSIMQ - Forbrig, Peter (Complex Systems Informatics and Modeling Quarterly, 2015)
For this issue we collected five papers that fall into the domain of Requirements Engineering. It is well known that wrong requirements cause a lot of problems. Some projects totally fail because of that, others waste a lot of money because the correction of resulted errors in the implementation is very time consuming and labour intensive. Therefore, new ideas in identifying the correct requirements are very important.